Stunting, FGD, PGD, Infeksi PENGARUH FGD (FOCUS GROUP DISCUSSION) DAN PGD (PEER GROUP DISCUSSION) TENTANG INFEKSI TERHADAP PENGETAHUAN DAN SIKAP IBU YANG MEMILIKI BALITA STUNTING DI DESA SIDOLUHUR KECAMATAN LAWANG KABUPATEN MALANG - amaliya rizqi (Jurnal Informasi Kesehatan Indonesia (JIKI), 2018)
Stunting toddler problems describe chronic nutritional problems, which are influenced by the condition of the mother or the prospective mother, the fetus, and the infant or toddler period, including the illness suffered during childhood. The result of Riskesdas 2013 shows the prevalence of stunting nationally in 2013 is 37.2 percent, while the prevalence of stunting in East Java is 27%. FGD and PGD are activities aimed at changing knowledge and attitude. The purpose of this study was to determine the effect of FGD and PGD on infections on the level of knowledge and attitude of mothers who have toddlers stunting in Sidoluhur Village. The type of this research is Quasy Experimental research using Two Group Pretest-Posttest Design. The study was conducted from October to November 2017. The result of this research indicates the influence of FGD on the increase of mother knew about the infection, this is proved by the result of the statistical test that is p-value <Î± (0,000 <0,05). There was a significant increase in the mean attitude of respondents at Î± 0.05 after FGD discussion. The existence of the influence of PGD on the increase of mother knew about the infection, this is proved by the result of the statistical test that is p-value <Î± (0,000 <0,05). There was a significant increase in mean attitudes of respondents at Î± 0.05 after discussion of PGD FGD and PGD are good if applied in the community considering the number of nutrition workers at Lawang Public Health Center is limited. The selection of peer tutors on PGD discussions was chosen because the peer tutors were more aware of the environmental conditions of the community directly.